A novel vehicle-mounted sticky trap; an effective sampling tool for savannah tsetse flies Glossina morsitans morsitans Westwood and Glossina morsitans centralis Machado. - Jackson Muyobela; Christian W W Pirk; Abdullahi A Yusuf; Njelembo J Mbewe; Catherine L Sole (Public Library of Science (PLoS), 2021)
Background Black screen fly round (BFR) is a mobile sampling method for Glossina morsitans. This technique relies on the ability of operator(s) to capture flies landing on the screen with hand nets. In this study, we aimed to evaluate a vehicle-mounted sticky panel trap (VST) that is independent of the operator's ability to capture flies against BFR, for effective and rapid sampling of G. m. morsitans Westwood and G. m. centralis Machado. We also determined the influence of the VST colour (all-blue, all-black or 1:1 blue-black), orientation and presence of odour attractants on tsetse catch. Methodology/principal findings Using randomised block design experiments conducted in Zambia, we compared and modelled the number of tsetse flies caught in the treatment arms using negative binomial regression. There were no significant differences in the catch indices of the three colour designs and for in-line or transversely oriented panels for both subspecies (P > 0.05). When baited with butanone and 1-octen-3-ol, VST caught 1.38 (1.11-1.72; P < 0.01) times more G. m. centralis flies than the un-baited trap. Attractants did not significantly increase the VST catch index for G. m. morsitans (P > 0.05). Overall, the VST caught 2.42 (1.91-3.10; P < 0.001) and 2.60 (1.50-3.21; P < 0.001) times more G. m. centralis and G. m. morsitans respectively, than the BFR. The VST and BFR took 10 and 35 min respectively to cover a 1 km transect. Conclusion/significance The VST is several times more effective for sampling G. m. morsitans and G. m. centralis than the BFR and we recommend its use as an alternative sampling tool.